Spatiality of the City in Literature: Possibilities and Limits of the Semiotic Approach - Kundrotaitė, Aušra (Respectus Philologicus, 2020)
The article attempts to delineate adequate ways of thinking about the spatiality of the city in literature. It examines two semiotic approaches to the problematic of the city, namely Jurij Lotman’s semiotics of culture and Algirdas Julius Greimas’ urban semiotics, and their applicability to the analysis of its literary representation. Lotman’s concept of semiosphere is invoked to outline the complex, two-way relationship between consciousness and the city. Highlighting the communicative and autocommunication processes of culture helps to establish a link with Greimas’ interpretive and generative methodological approaches. Both Greimas and Lotman treat the city as a virtual reality concentrating on the ideological, symbolical and philosophical aspects of it. Their theories regard language primarily as an acoustic phenomenon (as speech), and consequently tend to disregard its visual (e. g. graphic) features. The article considers possible combinations of the different branches of semiotics. The special attention is focused on demonstrating the importance of the (inter)medial aspects of the literary representation. A case study of the photo-essay helps to expose similarities and differences of the semiotic and the intermedial approaches. The article demonstrates how recognizing specific (inter)medial aspects of the text allows regarding the literary city as a topological object.